(3ZjK GdCOH GdPi GfSLe aj TQM GdGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s; (3eDjO GdOjf CHj ESeGYjd GdMSjf Hf Ydj aNQ GdcJGH GdYejO GdWZQGFj,J (B514 (3g` s ((3YHO GdefYe Hf NVQ GdeOfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH (B,(3HYO aEf GdbUjOI GdehSheI HdGejI GdYLe eeG JYGWi GdfGS bO CMHHJ Cf CVY YdjgG TQMkG s
(3BNQgG (B:s
(3hda ai GdHQOI CYWGag MJi jWjH GdfTQ ef dag Je TQM GdbUjOI GdeYQhaI HdGejI GdYLe s
(3GdfSNI HgG MhGTs
(3HgG HYV GdQShe GdObjbI GdeRjfI HChdgG agQSJs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdCHjGJ ajgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdCOHs